A Scoping Review on Ageing Migrants in Finland Through the Lens of Intersectionality and Vulnerability - Smarika KC; Kris Clarke; Marjaana Seppänen (Nordic Journal of Migration Research, 2023)
Finland is one of the most rapidly ageing countries in the world while concomitantly becoming a more diverse society through increased migration in recent decades. Concepts of ageing have often been constructed on a normative basis embedded in the narratives of Finland as a homogeneous society with universal services. These constructions render the needs of ageing migrants with diverse backgrounds invisible. This scoping review aims to identify and review the existing research on older migrants in Finland through the lens of intersectionality and vulnerability. It presents findings from 16 peer-reviewed publications, and sheds light on the paucity of research on ageing migrants in the Finnish context. Through a thematic analysis of a range of publications in this field, this review finds that research has not yet included the perspectives and lived experiences of diverse older migrants from marginal positions. The inequalities experienced by older migrants through multiple social identities and increased heterogeneity within the migrant groups are not captured enough in the Finnish literature. Older migrants report gaps in accessing services and struggle with discrimination. Rather than viewing ageing migrants as vulnerable, the study opens perspectives for future research to be more inclusive to the needs of growing diversity by adopting an intersectional approach and engaging older people from marginalized groups to understand key aspects of inequalities.